Adjuvant Systemic Chemotherapy vs Active Surveillance Following Up-front Resection of Isolated Synchronous Colorectal Peritoneal Metastases - Rovers, Koen P. (JAMA Oncol, 2020)
IMPORTANCE: To date, there are no data on the value of adjuvant systemic chemotherapy following up-front resection of isolated synchronous colorectal peritoneal metastases. OBJECTIVE: To assess the association between adjuvant systemic chemotherapy and overall survival following up-front resection of isolated synchronous colorectal peritoneal metastases. DESIGN, SETTING, AND PARTICIPANTS: In this population-based, observational cohort study using nationwide data from the Netherlands Cancer Registry (diagnoses between January 1, 2005, and December 31, 2017; follow-up until January 31, 2019), 393 patients with isolated synchronous colorectal peritoneal metastases who were alive 3 months after up-front complete cytoreductive surgery with hyperthermic intraperitoneal chemotherapy were included. Patients allocated to the adjuvant systemic chemotherapy group were matched (1:1) with those allocated to the active surveillance group by propensity scores based on patient-, tumor-, and treatment-level covariates. EXPOSURES: Adjuvant systemic chemotherapy, defined as systemic chemotherapy without targeted therapy, starting within 3 months postoperatively. MAIN OUTCOMES AND MEASURES: Overall survival was compared between matched groups using Cox proportional hazards regression analysis adjusted for residual imbalance. A landmark analysis was performed by excluding patients who died within 6 months postoperatively. A sensitivity analysis was performed to adjust for unmeasured confounding by major postoperative morbidity. RESULTS: Of 393 patients (mean [SD] age, 61 [10] years; 181 [46%] men), 172 patients (44%) were allocated to the adjuvant systemic chemotherapy group. After propensity score matching of 142 patients in the adjuvant systemic chemotherapy group with 142 patients in the active surveillance group, adjuvant systemic chemotherapy was associated with improved overall survival compared with active surveillance (median, 39.2 [interquartile range, 21.1-111.1] months vs 24.8 [interquartile range, 15.0-58.4] months; adjusted hazard ratio [aHR], 0.66; 95% CI, 0.49-0.88; P = .006), which remained consistent after excluding patients who died within 6 months postoperatively (aHR, 0.68; 95% CI, 0.50-0.93; P = .02) and after adjustment for major postoperative morbidity (aHR, 0.71; 95% CI, 0.53-0.95). CONCLUSIONS AND RELEVANCE: Findings of this study suggest that in patients undergoing up-front resection of isolated synchronous colorectal peritoneal metastases, adjuvant systemic chemotherapy appeared to be associated with improved overall survival. Although randomized trials are needed to address the influence of potential residual confounding and allocation bias on this association, results of this study may be used for clinical decision-making in this patient group for whom no data are available.